Active VSG Expression Sites in Trypanosoma brucei Are Depleted of Nucleosomes - Stanne, Tara M. (American Society for Microbiology (ASM), 2010)
African trypanosomes regulate transcription differently from other eukaryotes. Most of the trypanosome genome is constitutively transcribed by RNA polymerase II (Pol II) as large polycistronic transcription units while the genes encoding the major surface proteins are transcribed by RNA polymerase I (Pol I). In bloodstream form Trypanosoma brucei, the gene encoding the variant surface glycoprotein (VSG) coat is expressed in a monoallelic fashion from one of about 15 VSG bloodstream form expression sites (BESs). Little is known about the chromatin structure of the trypanosome genome, and the chromatin state of active versus silent VSG BESs remains controversial. Here, we determined histone H3 occupancy within the genome of T. brucei, focusing on active versus silent VSG BESs in the bloodstream form. We found that histone H3 was most enriched in the nontranscribed 50-bp and 177-bp repeats and relatively depleted in Pol I, II, and III transcription units, with particular depletion over promoter regions. Using two isogenic T. brucei lines containing marker genes in different VSG BESs, we determined that histone H3 is 11- to 40-fold depleted from active VSG BESs compared with silent VSG BESs. Quantitative PCR analysis of fractionated micrococcal nuclease-digested chromatin revealed that the active VSG BES is depleted of nucleosomes. Therefore, in contrast to earlier views, nucleosome positioning appears to be involved in the monoalleleic control of VSG BESs in T. brucei. This may provide a level of epigenetic regulation enabling bloodstream form trypanosomes to efficiently pass on the transcriptional state of active and silent BESs to daughter cells.